PENGARUH PUPUK ORGANIK LIMBAH KULIT KOPI (Coffea Arabica L.) TERHADAP PERTUMBUHAN BIBIT KOPI - Irham Falahudin; anita restu puji raharjeng; Lekat Harmeni (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
Coffee (coffea arabica) is one of source for foreign exchange in Indonesia and plays an important role in the development of industrial agriculture. The purpose of this study was to find out the effect of organic fertilizers from the waste of coffee skin in the planting medium on the growth of coffee seedlings and determine the optimal concentration of organic fertilizer which uses coffee skin on coffee seedling growth. This research was conducted in the field of coffee plantations, called Empat Lawang village using experimental methods with a completely randomized design (CRD), which consists of five treatments and five replications treatment, that are: P0 = Without additional of organic fertilizers from waste coffee skin (control) , P1 = with the addition of 5% (100 grams) organic fertilizer from waste coffee skin, P2 = Additional 10% (200 grams)organic fertilizer fromwaste coffee skin, P3 = with the addition of 15% (300 grams)organic fertilizers from waste coffee skin in, P4 = with the addition of 20% (400 grams)organic fertilizers from waste coffee skin. Data were analyzed with F test followed by LSD test (Least Significant Difference Test). The parameters of this study were plant height, leaf width, and number of leaves. The results showed that the additional of 20% (400 grams) (P4) organic fertilizers from waste coffee skin provides a very real effect on the growth of plant height, leaf width, and number of leaves. The conclusion was that organic fertilizers from waste coffee skin20% (400 grams) provide maximum growth of the coffee plant.